Connecting Connecting Local Wisdom and Social Media: Innovative Strategies in Building Economic Sustainability and Overcoming Unemployment - Nurhalimah Harahap; Atika Hanan Julia Harahap (Universitas Pendidikan Ganesha, 2024)
The mismatch between the skills possessed by job seekers and the needs of the labor market causes unemployment. Based on this, this study aims to explore innovative strategies that connect local wisdom with social media to build economic sustainability and overcome unemployment. A mixed-method approach was used in this study. The three elements of local wisdom that are the focus of this study are Paloh Naga Agrotourism, Selayar Denai, and Pasar Kamu. The number of respondents was determined by as many as 30 people selected using the purposive sampling technique. The data collection method used questionnaires, interviews, and observations. The data collection instrument used a questionnaire sheet. The data analysis technique used qualitative and quantitative descriptive analysis. The study results showed that using social media, such as Instagram and Facebook, significantly increased the visibility and tourist visits to the agrotourism location. Social media is an effective promotional tool that introduces local uniqueness and opens up new jobs for the local community, both Generation Z and millennials. Combining local wisdom and digital strategies, this village has succeeded in increasing economic resilience by sustainably utilizing local natural and cultural potential. It is concluded that the synergy between local wisdom and social media supports economic growth in Kampoeng Lama Tourism Village and contributes to overcoming unemployment. This study's recommendation is to strengthen local communities' digital capacity and further develop elements of local wisdom to create a more integrated and inclusive tourism ecosystem.